Consequences of Maternal Mortality on Families in the Rural Communities in Enugu State - Nkechi , M. Okeke; Beatrice , N. Onah; Ngozi , F. Nnaji (International Journal of Psychosocial Rehabilitation, 2021)
he purpose of the study was to expose the consequences of maternal mortality on rural communities in Enugu State Nigeria. One research question was used to identify the consequences of maternal mortality. A survey design was used and data was collected using a questionnaire. A total of 108 pregnant women participated in the study. Data were analyzed using mean and standard deviation. The study revealed an increase in juvenile delinquency because of lack of motherly upbringing, reduction in population, maternal death leaves the man lonely in the family, increase in the number of motherless babies, economic drains derived from maternal death, increase in depression on the part of the man, the older children are likely to drop out of school etc. Based on the study, the following recommendations were made: family members and non-governmental organizations should reduce the burden of maternal death on families through financial support and public health attention; women should access family planning and adequate health care during pregnancy and delivery; the government and non-governmental organizations should support Safe Motherhood Initiatives in the rural communities